On the classification of phacomatosis pigmentovascularis - Torchia, D. (European Journal of Pediatric Dermatology, 2022)
The author reviews the traditional classification of FPV in the light of Happle's most recent classification (2) and its updates (6), which stand up to time and scientific evidence. This classification (Table 1) should be the only one used both in clinical practice and in research until proven otherwise.